Revised Shyness Scale (ETR-13): Psychometric Properties in Peruvian Adolescents - Olivas-Ugarte, Lincol Orlando (2022)
Background: shyness can interfere with the normal development of social relationships during adolescence, and negatively affect self-concept during schooling; therefore, it is necessary to have valid, reliable, equitable measuring instruments and normative conditions for their appropriate use in the Peruvian context. Objective: this instrumental research aimed at analyzing the psychometric properties of the Revised Shyness Scale (ETR13) and generating normative data for its application in adolescents from Lima Metropolitan Area. Method: five hundred (500) adolescents aged between 12 and 17 (M = 14.65, SD = 1.60) participated in the study, out of which 205 (41%) were males and 295 (59%) females. Results: the results of the confirmatory factor analysis showed acceptable values for a second-order model: χ2 /df = 1.41, CFI = .996, TLI = .995, RMSEA = .029 and SRMR = .035. Convergent validity was verified with the Social Anxiety Scale for Adolescents (SAS-A) (r = .674; r2 = .25) and divergent validity with the Academic Self-Concept Scale (EAA) (r = -.436; r2 = .19). Consequently, the reliability was obtained by the ordinal omega coefficient for the general scale (ω = .90) and its two factors (ω = .89 and ω = .77). Conclusions: a factorial invariance analysis made it possible to demonstrate the equivalence of the instrument by sex and age (ΔCFI < .01, ΔRMSEA < .01). Therefore, it is concluded that ETR-13 has adequate psychometric properties to evaluate the shyness variable in the target population. Authorship contributionThe authors participated in the entire development of the article.